Heat capacity measurements on BaTa2O6 and derivation of its thermodynamic functions - SARIOĞLU, CEVAT (SPRINGER, 2017)
Heat capacity measurements of barium tantalate (BaTa2O6) were carried out by using a differential scanning calorimeter at temperatures between 323 and 1323 K. From the heat capacity values of BaTa2O6, other thermodynamic functions (enthalpy and entropy increments) were derived between 298.15 and 1323 K. The C (p,m) (298.15) value of BaTa2O6 was computed as 184.857 J mol(-1) K-1. Moreover, fitted heat capacities exhibited good agreement with Neumann-Kopp rule at the temperatures between 298.15 and 1300 K.
Keywords: BaTa2O6; Oxides; DSC; Heat capacity; Thermodynamic properties; PHASE